Nanocellulose masterbatch and method for producing the same
By using surface-treated nanocellulose and dispersant in the nanocellulose masterbatch, the problem of difficulty in homogeneous dispersion and viscosity increase in nanocellulose in the rubber composition is solved, and excellent tensile properties and easy mixing characteristics are achieved.
Patent Information
- Application Number
- CN202280023234.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2021-04-07
- Filing Date
- 2022-03-30
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2042-03-30
AI Technical Summary
Nanocellulose is prone to agglomeration during solidification and drying, resulting in difficulty in dispersing homogeneously in the rubber composition, and the resulting nanocellulose masterbing viscosity increases, making it difficult to mix with other materials.
Nanocellulose containing rubber components, resorcinol-formaldehyde initial condensate of resorcinol-formaldehyde and formaldehyde surface treatment is used, and a dispersant is added to control the dispersion and viscosity of the nanocellulose through specific mixing and processes.
The homogeneous dispersion of nanocellulose is achieved, the viscosity increase is suppressed, and the rubber composition with excellent tensile stress and elongation is obtained, and mixing with other materials becomes easier.
Smart Images

Figure CN117083333B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a nanocellulose masterbatch, a method for producing the same, and a rubber composition using the nanocellulose masterbatch. Background Art
[0002] Rubber compositions constituting tires etc. are required to have excellent properties such as elastic modulus (elongation) and hardness (hardness). Furthermore, in order to improve such properties, a technique of mixing a filler such as carbon black or silica into a rubber composition is known.
[0003] Furthermore, a technique for mixing nanocellulose, which is an extremely fine fiber of cellulose, into a rubber composition as a filler has also been developed. For example, Patent Document 1 discloses that a rubber composition having excellent processability, good balance of rigidity, fracture characteristics, and low fuel consumption can be provided by dispersing chemically modified microfibril cellulose having a cationic group into a rubber composition.
[0004] Prior art literature
[0005] Patent Literature
[0006] Patent Document 1: Japanese Patent No. 6353169 Summary of the invention
[0007] Problems to be solved by the invention
[0008] However, nanocellulose is easy to agglomerate and bunch in the process of removing water such as solidification and drying, so in the manufacture of the masterbatch (nanocellulose masterbatch) comprising nanocellulose, the nanocellulose contained is difficult to be dispersed homogeneously and keeps being divided into filaments until the state of nanometer level. In addition, the viscosity of the nanocellulose masterbatch obtained sometimes rises, and it is difficult to mix with other materials (particularly other rubber components). Therefore, the nanocellulose masterbatch that obtains nanocellulose is dispersed homogeneously and keeps being divided into filaments until the state of nanometer level is useful because it can obtain the rubber composition that tensile stress and elongation are all excellent, in addition, the viscosity rise of such nanocellulose masterbatch is suppressed because mixing with other materials is easy to carry out, and the making of rubber composition becomes easy, and therefore is also useful. And then, in the preparation method of nanocellulose masterbatch in the past, there is room for further improvement in these aspects.
[0009] Therefore, an object of the present invention is to provide a nanocellulose masterbatch in which nanocellulose is uniformly dispersed, an increase in viscosity is suppressed, and a rubber composition excellent in tensile stress and elongation can be obtained.
[0010] Methods for solving problems
[0011] In order to solve the above-mentioned problems, the present inventors conducted intensive research and found that the nanocellulose of the following nanocellulose masterbatch is homogeneously dispersed and the viscosity increase is also suppressed, and a rubber composition excellent in tensile stress and elongation can be obtained, thereby completing the present invention. The above-mentioned nanocellulose masterbatch contains a rubber component, nanocellulose surface-treated with a resol type and / or novolac type resorcinol-formaldehyde initial condensate and formaldehyde, and a dispersant, and the rubber component contains natural rubber or styrene-butadiene copolymer rubber as a main component, relative to 100 parts by mass of the rubber component, contains 0.3 to 60 parts by mass of nanocellulose, 0.5 to 35 parts by mass of the dispersant, and relative to 1 part by mass of the nanocellulose, contains 0.03 to 1.2 parts by mass of a resol type and / or novolac type resorcinol-formaldehyde initial condensate and 0.02 to 0.8 parts by mass of formaldehyde.
[0012] That is, the present invention is the following <1> to <13>.
[0013] <1> A nanocellulose masterbatch comprising a rubber component, nanocellulose surface-treated with a resol type and / or novolac type resorcinol-formaldehyde initial condensate and formaldehyde, and a dispersant, wherein the rubber component contains natural rubber or styrene-butadiene copolymer rubber as a main component, and the nanocellulose is contained in an amount of 0.3 to 60 parts by mass and 0.5 to 35 parts by mass of the dispersant per 100 parts by mass of the rubber component, and the nanocellulose is contained in an amount of 0.03 to 1.2 parts by mass of the resol type and / or novolac resorcinol-formaldehyde initial condensate and 0.02 to 0.8 parts by mass of the formaldehyde per 1 part by mass of the nanocellulose.
[0014] <2> The nanocellulose masterbatch according to <1>, wherein the dispersant is a fatty acid derivative mixture, and the dispersant is contained in an amount of 0.5 to 10 parts by mass based on 100 parts by mass of the rubber component.
[0015] <3> The nanocellulose masterbatch according to <1>, wherein the dispersant is a low molecular weight diene liquid polymer having a weight average molecular weight of 2,000 to 60,000, and the dispersant is contained in an amount of 1 to 35 parts by mass based on 100 parts by mass of the rubber component.
[0016] <4> According to the nanocellulose masterbatch described in <1>, the above-mentioned dispersant is one or more selected from oil, alkylphenol-formaldehyde resin, petroleum resin, rosin, rosin-modified resin, coumarone-indene resin, terpene resin, and lignin, and the above-mentioned dispersant is contained in 1 to 30 parts by mass relative to 100 parts by mass of the above-mentioned rubber component.
[0017] <5>A method for producing a nanocellulose masterbatch is the method for producing a nanocellulose masterbatch described in any one of <1> to <4>, comprising the following steps: a step of mixing a rubber latex of natural rubber or styrene-butadiene copolymer rubber, a latex of styrene-butadiene copolymer rubber and / or styrene-butadiene-vinylpyridine terpolymer, an RF latex consisting of a resol type and / or novolac type resorcinol-formaldehyde initial condensate and formaldehyde, nanocellulose, and a dispersant to obtain a raw dispersion; a step of coagulating the raw dispersion to obtain a coagulant; and a step of drying the coagulant to obtain a dried product.
[0018] <6>A method for producing a nanocellulose masterbatch is the method for producing a nanocellulose masterbatch described in any one of <1> to <4>, comprising the following steps: a step of mixing a rubber latex of natural rubber or styrene-butadiene copolymer rubber, a latex of a styrene-butadiene copolymer rubber and / or a styrene-butadiene-vinylpyridine terpolymer, an RF latex consisting of a resol type and / or a phenolic varnish type resorcinol-formaldehyde initial condensate and formaldehyde, and nanocellulose to obtain a raw material dispersion; a step of coagulating the raw material dispersion to obtain a coagulant, and then mixing a dispersant; and a step of drying the coagulant mixed with the dispersant to obtain a dried product.
[0019] <7>A method for producing a nanocellulose masterbatch is the method for producing a nanocellulose masterbatch described in any one of <1> to <4>, comprising the following steps: a step of mixing a rubber latex of natural rubber or styrene-butadiene copolymer rubber, a latex of a styrene-butadiene copolymer rubber and / or a styrene-butadiene-vinylpyridine terpolymer, an RF latex consisting of a resol type and / or a phenolic varnish type resorcinol-formaldehyde initial condensate and formaldehyde, and nanocellulose to obtain a raw material dispersion; a step of coagulating the raw material dispersion to obtain a coagulant; and a step of drying the coagulant to obtain a dried product, and then mixing a dispersant.
[0020] <8>A method for producing a nanocellulose masterbatch is the method for producing a nanocellulose masterbatch described in any one of <1> to <4>, comprising the following steps: a step of mixing a latex composed of styrene-butadiene copolymer rubber and / or styrene-butadiene-vinylpyridine terpolymer, a RF latex consisting of a resole phenolic resin type and / or a phenolic varnish type resorcinol-formaldehyde initial condensate and formaldehyde, nanocellulose, and a dispersant to obtain a mixed solution; a step of coagulating a raw material dispersion obtained by mixing a rubber latex of natural rubber or styrene-butadiene copolymer rubber with the above-mentioned mixed solution to obtain a coagulant; and a step of drying the above-mentioned coagulant to obtain a dried product.
[0021] <9>A method for producing a nanocellulose masterbatch is the method for producing a nanocellulose masterbatch according to any one of <1> to <4>, comprising the following steps: a step of mixing a latex of styrene-butadiene copolymer rubber and / or styrene-butadiene-vinylpyridine terpolymer, an RF latex consisting of a resole phenolic resin type and / or a phenolic varnish type resorcinol-formaldehyde initial condensate and formaldehyde, and nanocellulose to obtain a mixed solution; a step of coagulating a raw material dispersion obtained by mixing a rubber latex of natural rubber or styrene-butadiene copolymer rubber and a dispersant in the mixed solution to obtain a coagulant; and a step of drying the coagulant to obtain a dried product.
[0022] <10>A method for producing a nanocellulose masterbatch is the method for producing a nanocellulose masterbatch according to any one of <1> to <4>, comprising the following steps: a step of mixing a latex of styrene-butadiene copolymer rubber and / or styrene-butadiene-vinylpyridine terpolymer, an RF latex consisting of a resorcinol-formaldehyde initial condensate of a resol type and / or a phenolic varnish type and formaldehyde, and nanocellulose to obtain a mixed solution; a step of coagulating a raw material dispersion obtained by mixing a rubber latex of natural rubber or styrene-butadiene copolymer rubber with the mixed solution to obtain a coagulant, and then mixing a dispersant; and a step of drying the coagulant mixed with the dispersant to obtain a dried product.
[0023] <11>A method for producing a nanocellulose masterbatch is the method for producing a nanocellulose masterbatch described in any one of <1> to <4>, comprising the following steps: a step of mixing a latex composed of a styrene-butadiene copolymer rubber and / or a styrene-butadiene-vinylpyridine terpolymer, an RF latex composed of a resorcinol-formaldehyde initial condensate of a resol type and / or a phenolic varnish type and formaldehyde, and nanocellulose to obtain a mixed solution; a step of coagulating a raw material dispersion obtained by mixing a rubber latex of a natural rubber or a styrene-butadiene copolymer rubber with the mixed solution to obtain a coagulant; and a step of drying the coagulant to obtain a dried product, and then mixing a dispersant.
[0024] <12> A rubber composition obtained by using the nanocellulose masterbatch described in any one of <1> to <4> and a rubber component, wherein the rubber component contains 25 parts by mass or more of natural rubber and / or isoprene rubber per 100 parts by mass of the total rubber component, and the rubber component contains 0.3 to 60 parts by mass of nanocellulose and 30 to 200 parts by mass of carbon black and / or silica relative to 100 parts by mass of the total rubber component.
[0025] <13> A rubber composition obtained by using the nanocellulose masterbatch described in any one of <1> to <4> and a rubber component, wherein the rubber component contains 35 parts by mass or more of styrene-butadiene copolymer rubber and / or styrene-butadiene-vinylpyridine terpolymer among 100 parts by mass of the total rubber component, and the mass ratio of the styrene-butadiene copolymer rubber and / or styrene-butadiene-vinylpyridine terpolymer is the highest among the above-mentioned total rubber components, and the rubber component contains 0.3 to 60 parts by mass of nanocellulose and 30 to 200 parts by mass of carbon black and / or silica relative to 100 parts by mass of the above-mentioned total rubber components.
[0026] Effects of the Invention
[0027] According to the present invention, a nanocellulose masterbatch can be obtained in which nanocellulose is uniformly dispersed and an increase in viscosity is suppressed, and a rubber composition having excellent tensile stress and elongation can be obtained. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 The diagrams schematically show the states of the rubber component (large circle shape) and nanocellulose (wire shape) in the nanocellulose masterbatch prepared in the examples. (a) is a schematic diagram of C1-6, and (b) is a schematic diagram of E1-1. DETAILED DESCRIPTION
[0029] The present invention will be described.
[0030] The present invention is a nanocellulose masterbatch, a method for producing the same, and a rubber composition using the nanocellulose masterbatch, wherein the nanocellulose masterbatch contains a rubber component, nanocellulose surface-treated with a resol-type and / or novolac-type resorcinol-formaldehyde initial condensate and formaldehyde, and a dispersant, wherein the rubber component contains natural rubber or styrene-butadiene copolymer rubber as a main component, and contains 0.3 to 60 parts by mass of nanocellulose and 0.5 to 35 parts by mass of dispersant relative to 100 parts by mass of the rubber component, and contains 0.03 to 1.2 parts by mass of a resol-type and / or novolac-type resorcinol-formaldehyde initial condensate and 0.02 to 0.8 parts by mass of formaldehyde relative to 1 part by mass of the nanocellulose. Hereinafter, it is also referred to as "the nanocellulose masterbatch of the present invention", "the method for producing the nanocellulose masterbatch of the present invention", and "the rubber composition of the present invention".
[0031] In addition, unless otherwise specified, the numerical range expressed using "to" in the present invention means a numerical range having the numerical value described before "to" as the lower limit and the numerical value described after "to" as the upper limit.
[0032] <Nanocellulose masterbatch of the present invention>
[0033] First, the raw materials, component composition, etc. of the nanocellulose masterbatch of the present invention are described. The nanocellulose masterbatch of the present invention is prepared using at least a predetermined rubber latex, RF latex, nanocellulose, and a dispersant as raw materials. Each of them is described in detail below.
[0034] [Rubber latex]
[0035] In the nanocellulose masterbatch of the present invention, the rubber latex of natural rubber (NR) or styrene-butadiene copolymer rubber (SBR) is used as raw material. In addition, so-called latex is an aqueous dispersion in which the rubber component is colloidally dispersed in water. Then, in the case of making the rubber composition of the present invention using the rubber component together with the nanocellulose masterbatch of the present invention obtained, the rubber component of the rubber latex is suitable for being identical with the rubber component mixed with the rubber composition of the present invention. That is, in the case of making the rubber composition of the present invention using the nanocellulose masterbatch of the present invention and natural rubber, the nanocellulose masterbatch of the present invention preferably uses the latex of natural rubber as rubber latex, and in the case of making the rubber composition of the present invention using the nanocellulose masterbatch of the present invention and styrene-butadiene copolymer rubber, the nanocellulose masterbatch of the present invention preferably uses the latex of styrene-butadiene copolymer rubber as rubber latex.
[0036] Furthermore, the weight average molecular weight of the natural rubber or styrene-butadiene copolymer rubber is preferably 50,000 to 3,000,000, and more preferably 100,000 to 2,000,000.
[0037] Here, the so-called "weight average molecular weight" in the present invention refers to a value measured by gel permeation chromatography (GPC) using tetrahydrofuran as a solvent in terms of standard polystyrene. In addition, the GPC measurement uses a column (made by Polymer Laboratories, MIXED-B) as a measuring instrument and is performed at 40°C. The same applies to the following.
[0038] Furthermore, the nanocellulose masterbatch of the present invention is produced by using the rubber latex as the main raw material (a raw material accounting for more than 60% by mass of the solid content of all raw materials), so the rubber component contained in the nanocellulose masterbatch of the present invention contains natural rubber or styrene-butadiene copolymer rubber as the main component. That is, in the case of using the latex of natural rubber as the rubber latex, the rubber component contained in the nanocellulose masterbatch of the present invention contains natural rubber as the main component, and in the case of using the latex of styrene-butadiene copolymer rubber as the rubber latex, the rubber component contained contains styrene-butadiene copolymer rubber as the main component.
[0039] Here, the so-called "comprising... as a main component" means that the rubber component contained in the nanocellulose masterbatch of the present invention comprises 60% by mass or more of the rubber component, and the ratio is preferably 70% by mass or more, more preferably 80% by mass or more, further preferably 90% by mass or more, further preferably 95% by mass or more, and further preferably 98% by mass or more.
[0040] [RF latex]
[0041] In the nanocellulose masterbatch of the present invention, RF latex is further used as raw material. The RF latex is composed of a latex of a styrene-butadiene copolymer rubber and / or a styrene-butadiene-vinyl pyridine terpolymer, a resol type and / or a novolac type resorcinol-formaldehyde initial condensate (RF resin) and formaldehyde, and can be obtained by making the latex of a styrene-butadiene copolymer rubber and / or a styrene-butadiene-vinyl pyridine terpolymer contain RF resin and formaldehyde or formalin (aqueous formaldehyde solution).
[0042] The so-called "resorcinol-formaldehyde initial condensate" is a condensate (oligomer) obtained by condensing resorcinol and formaldehyde in the presence of a catalyst as a phenolic resin, and its degree of polymerization is preferably about 5 to 15. Furthermore, the resorcinol-formaldehyde initial condensate may contain unreacted resorcinol and / or formaldehyde.
[0043] In addition, a condensation product having methylol groups obtained by condensing resorcinol-formaldehyde at a molar ratio of 1 / 1 to 3 under an alkali catalyst such as sodium hydroxide or sodium carbonate is a resorcinol-formaldehyde initial condensation product of the resorcinol-formaldehyde type (a condensation product represented by the following formula (1) (where n is the degree of polymerization)). On the other hand, a condensation product having no methylol groups obtained by condensing resorcinol-formaldehyde at a molar ratio of 1 / 0.8 to 0.9 under an acid catalyst such as oxalic acid is a novolac type resorcinol-formaldehyde initial condensation product (a condensation product represented by the following formula (2) (where m is the degree of polymerization)). In the present invention, the resorcinol-formaldehyde initial condensation product may be either a resorcinol type or a novolac type, but a novolac type is preferred.
[0044]
[0045] [Other rubber components]
[0046] Nanocellulose masterbatch of the present invention is as mentioned above, and the rubber component included includes natural rubber or styrene-butadiene copolymer rubber as principal component, but as long as in this way, in nanocellulose masterbatch of the present invention, the rubber component (diene rubber component except natural rubber and styrene-butadiene copolymer rubber etc.) except natural rubber and styrene-butadiene copolymer rubber can be included. In this case, the rubber component can be included in above-mentioned rubber latex, RF latex, or the latex of other rubber components can be used as raw material. In addition, the content of the rubber component except natural rubber and styrene-butadiene copolymer rubber is preferably less than 30 mass % among the rubber component overall included by nanocellulose masterbatch of the present invention, more preferably less than 20 mass %, further preferably less than 10 mass %, further preferably less than 5 mass %, further preferably less than 2 mass %.
[0047] [Nanocellulose]
[0048] In the nanocellulose masterbatch of the present invention, nanocellulose is further used as a raw material. The so-called "nanocellulose" refers to ultrafine fibers with an average fiber diameter of 1 to 1000 nm composed of cellulose microfibrils, including: amorphous cellulose nanofibers (CNF) with an average fiber length of 0.5 to 5 μm, crystalline cellulose nanocrystals (CNC) with an average fiber length of 0.1 to 0.5 μm, etc.
[0049] In addition, in the nanocellulose masterbatch of the present invention, the nanocellulose is mixed with the above-mentioned RF latex to become nanocellulose surface-treated with the RF resin and formaldehyde contained in the RF latex. Hereinafter, the nanocellulose surface-treated with the RF resin and formaldehyde is sometimes referred to as "nanocellulose".
[0050] Furthermore, the average fiber diameter of the nanocellulose is 1 to 1000 nm as described above, but is preferably 1 to 200 nm. In addition, the average aspect ratio (average fiber length / average fiber diameter) of the nanocellulose is preferably 10 to 1000, more preferably 50 to 500. If the average fiber diameter is less than the above range and / or the average aspect ratio exceeds the above range, the dispersibility of the nanocellulose tends to be easily reduced. In addition, if the average fiber diameter exceeds the above range and / or the average aspect ratio is less than the above range, the reinforcing performance of the nanocellulose tends to be easily reduced.
[0051] Here, the "average fiber diameter" and "average fiber length" of nanocellulose in the present invention refer to the average value of the fiber diameter and fiber length of at least 50 fibers measured in an electron microscope image obtained by TEM observation or SEM observation at a magnification appropriately set according to the size of the constituent fibers. Furthermore, the average aspect ratio is calculated from the average fiber length and average fiber diameter obtained in this manner.
[0052] In addition, the cellulose that becomes the raw material of the nanocellulose can be any of wood or non-wood (bacteria, algae, cotton, etc.) sources, without particular limitation. As a method for making nanocellulose, examples include, for example, adding water to the cellulose that becomes the raw material, treating it by a mixer, etc., modulating a slurry in which the cellulose is dispersed in water, and directly applying mechanical shearing force to it through a high-pressure type, ultrasonic type, etc. device to separate the fibers; applying chemical treatments such as oxidation treatment, alkali treatment, and acid hydrolysis to the slurry, modifying the cellulose so that it is easy to separate the fibers, and then applying mechanical shearing force to separate the fibers through a disperser, etc. In this way, by separating the fibers after chemical treatment, the cellulose can be separated more finely and homogeneously with low energy, and chemically modified nanocellulose (chemically modified nanocellulose) can be easily obtained. In addition, as chemical treatment, for example, treatment with chemical treatment agents such as 2,2,6,6-tetramethylpiperidin-1-oxyl (hereinafter referred to as "TEMPO"), 4-acetamide-TEMPO, 4-carboxyl-TEMPO, 4-amino-TEMPO, 4-hydroxy-TEMPO, 4-phosphonooxy-TEMPO, phosphate, periodic acid, alkali metal hydroxide and carbon disulfide can be cited. In addition, chemical treatment can be performed after mechanical fiber splitting of cellulose. Furthermore, in addition to the above-mentioned chemical treatment, in order to further improve the affinity with rubber components, cellulase treatment, carboxyl methylation, esterification, treatment with cationic polymers, etc. can also be implemented after the fiber splitting process.
[0053] In the present invention, from the perspective of further improving the affinity with RF resins, etc., it is preferred to use chemically modified nanocellulose having one or more groups selected from carboxyl groups, phosphate groups, phosphite groups, xanthate groups, sulfone groups, sulfate groups, and thiolate groups (for example, oxidized cellulose nanofibers in which a part of the hydroxyl groups are oxidized to polar groups such as carboxyl groups, aldehyde groups, phosphate groups, phosphite groups, and xanthate groups). In particular, it is more preferred to use chemically modified nanocellulose having a carboxyl group.
[0054] [Dispersant]
[0055] In the nanocellulose masterbatch of the present invention, a dispersant is further used as a raw material. The dispersant is a component that further improves the dispersibility of the nanocellulose surface-treated with the RF resin and formaldehyde in the rubber component.
[0056] The dispersant is not limited, but suitable ones include fatty acid derivatives or fatty acid derivative mixtures, low molecular weight diene liquid polymers having a weight average molecular weight of 2,000 to 60,000, or one or more selected from oils, alkylphenol-formaldehyde resins, petroleum resins, rosin, rosin-modified resins, coumarone-indene resins, terpene resins, and lignin.
[0057] In addition, as long as the fatty acid derivative mixture is a mixture of multiple compounds comprising more than one fatty acid derivative, it is not limited, but from the viewpoint that the dispersibility of nanocellulose improves, it is more preferably a fatty acid derivative mixture comprising metal soap as the main component. Examples may include, for example, a fatty acid derivative mixture comprising calcium soap as the main component, a fatty acid derivative mixture comprising zinc soap as the main component. In addition, it is also preferred to comprise a fatty acid derivative mixture of fatty acid amide, fatty acid ester, etc., more preferably a fatty acid derivative mixture comprising more than 2 such fatty acid derivatives. However, fatty acid derivatives such as metal soap, fatty acid amide, fatty acid ester can be used alone. And then, the fatty acid forming the fatty acid derivative can be a saturated fatty acid, or can also be an unsaturated fatty acid.
[0058] Here, “containing a metal soap as a main component” means containing 60% by mass or more of the metal soap, and the proportion is preferably 70% by mass or more, more preferably 80% by mass or more, and further preferably 90% by mass or more.
[0059] In addition, the low molecular weight diene liquid polymer having a weight average molecular weight of 2000 or more and 60000 or less is not particularly limited as long as it is a liquid diene polymer having a weight average molecular weight within the above range. Examples thereof include liquid polyisoprene, liquid polybutadiene, liquid styrene-butadiene copolymer, etc. Furthermore, it may be a substance whose terminal is modified (for example, the terminal group is any one of hydroxyl, carboxyl, amino, and methacryloyl), and is particularly suitable for a low molecular weight diene liquid polymer whose terminal is not modified, or a low molecular weight diene liquid polymer whose terminal group is hydroxyl or carboxyl.
[0060] Further, as oil, aromatic oil, paraffin oil, naphthenic oil, etc. can be exemplified as preferred substances. As alkylphenol-formaldehyde resins, phenols with alkyl groups with carbon atoms of 1 or more and 18 or less obtained from cresol, isopropylphenol, tert-butylphenol, amylphenol, p-octylphenol (tert-octylphenol), nonylphenol, dodecylphenol, allylphenol, cyclohexylphenol, 4,6-dioctylresorcin, etc., and phenolic resins of various derivatives such as their hydroxymethylated derivatives and halogenated derivatives, etc. can be exemplified as preferred substances. As petroleum resins, C5 fraction petroleum resins, C9 fraction petroleum resins, C5 / C9 fraction petroleum resins, DCPD (dicyclopentadiene: dicyclopentadiene) petroleum resins, etc. can be exemplified as preferred substances. As terpene resins, terpene resins, aromatic modified terpene resins, terpene phenol resins, hydrogenated terpene resins, hydrogenated terpene phenol resins, etc. can be exemplified as preferred substances.
[0061] In addition, rosin is a kind of natural resin also called rosin. In addition, rosin-modified resin is a resin modified by the rosin. Furthermore, coumarone-indene resin is a resin obtained by polymerizing coumarone and indene. Furthermore, lignin is an aromatic polymer constituting the main component of a plant body.
[0062] Furthermore, from the viewpoint of being able to more easily function as a dispersant, the oil or resin preferably has a softening point of 60 to 150° C. The softening point of the oil or resin is measured by a method in accordance with JIS K6220-1:2015.
[0063] [Ingredients]
[0064] The composition of each component in the nanocellulose masterbatch of the present invention produced using the above-mentioned raw materials is as follows.
[0065] First, relative to 100 parts by mass of the rubber component, as the solid content of nanocellulose, 0.3 to 60 parts by mass, preferably 0.5 to 55 parts by mass, more preferably 1 to 50 parts by mass, further preferably 3 to 45 parts by mass, further preferably 5 to 40 parts by mass of nanocellulose are contained. If the content of nanocellulose is too little, the possibility that the mechanical properties of the rubber composition obtained by using the nanocellulose masterbatch cannot be fully improved is high. In addition, if the content of the nanocellulose is too much, there is the possibility that the nanocellulose cannot be homogeneously dispersed, and further, there is the possibility that the cost of the obtained nanocellulose masterbatch becomes high. Furthermore, there is also the possibility that the viscosity of the obtained nanocellulose masterbatch rises and it is difficult to mix with other materials.
[0066] In addition, the dispersant is contained in an amount of 0.5 to 35 parts by mass, preferably 0.8 to 35 parts by mass, more preferably 1 to 30 parts by mass, further preferably 1 to 20 parts by mass, and further preferably 1 to 10 parts by mass, relative to 100 parts by mass of the rubber component. In particular, when a fatty acid derivative or a fatty acid derivative mixture is used as the dispersant, it is suitable to contain it in an amount of 0.5 to 10 parts by mass, further preferably 1 to 5 parts by mass, relative to 100 parts by mass of the rubber component. Furthermore, when a low molecular weight diene liquid polymer having a weight average molecular weight of 2,000 to 60,000 is used as the dispersant, it is suitable to contain it in an amount of 1 to 35 parts by mass, further preferably 5 to 25 parts by mass, relative to 100 parts by mass of the rubber component. Furthermore, when one or more selected from oil, alkylphenol-formaldehyde resin, petroleum resin, rosin, rosin-modified resin, coumarone-indene resin, terpene resin, and lignin are used as the dispersant, it is suitable to contain it in an amount of 1 to 30 parts by mass, and further 3 to 20 parts by mass, relative to 100 parts by mass of the rubber component.
[0067] Here, the so-called "100 parts by mass of rubber component" refers to the case where the total mass of the natural rubber or styrene-butadiene copolymer rubber derived from rubber latex contained in the nanocellulose masterbatch of the present invention (solid content), the mass of styrene-butadiene copolymer rubber and / or styrene-butadiene-vinylpyridine terpolymer derived from RF latex (solid content), and the mass (solid content) of the rubber component when the above-mentioned other rubber components are included is set to 100 parts by mass.
[0068] In addition, RF resin and formaldehyde are based on the mass (solid content) of nanocellulose. Specifically, relative to 1 mass part of nanocellulose, RF resin contains 0.03 to 1.2 mass parts, preferably 0.05 to 0.8 mass parts, more preferably 0.06 to 0.6 mass parts, and more preferably 0.08 to 0.4 mass parts, and 0.02 to 0.8 mass parts, preferably 0.03 to 0.5 mass parts, more preferably 0.04 to 0.4 mass parts, and more preferably 0.05 to 0.3 mass parts of formaldehyde. In the case where the above-mentioned unreacted formaldehyde is included in the RF resin, the unreacted formaldehyde is also included in the formaldehyde content. If they are too few, there is a possibility that the surface treatment of nanocellulose cannot be fully carried out and the dispersibility of nanocellulose is reduced. In addition, if they are too many, there is a possibility that the mechanical properties of the rubber composition obtained by the nanocellulose masterbatch cannot be fully improved.
[0069] In addition, although not limited, in the nanocellulose masterbatch of the present invention, from the perspective of facilitating the above-mentioned component composition, the RF latex used as the above-mentioned raw material is preferably a composition in which the solid content of styrene-butadiene copolymer rubber and / or styrene-butadiene-vinylpyridine terpolymer is 70 to 95% by mass, the RF resin is 4 to 24% by mass, and the formaldehyde is 1 to 6% by mass.
[0070] <Method for producing nanocellulose masterbatch of the present invention>
[0071] Next, the method for producing the nanocellulose masterbatch of the present invention will be described.
[0072] The method for producing a nanocellulose masterbatch of the present invention uses the rubber latex, RF latex, nanocellulose, and a dispersant as raw materials, but can be roughly divided into the following I to VII depending on the timing of adding (mixing) the dispersant or rubber latex. Each is described in detail below.
[0073] [Manufacturing method I]
[0074] In this manufacture method I, first, the rubber latex of natural rubber or styrene-butadiene copolymer rubber, the above-mentioned RF latex, nanocellulose and dispersant are all put into mixer etc. at the same time and mixed. In addition, the solid content of rubber latex and RF latex at this time is preferably below 60 mass %, more preferably below 50 mass %. In addition, from the viewpoint of the ease of mixing with RF latex etc., nanocellulose is suitable for being put into and mixed after being made into nanocellulose aqueous dispersion, and the nanocellulose content (solid content of nanocellulose) of this nanocellulose aqueous dispersion is preferably 0.1~10 mass %, more preferably 0.1~5 mass %. Particularly, cellulose nanofiber is suitable for using cellulose nanofiber aqueous dispersion as nanocellulose aqueous dispersion because it is easy to be made into aqueous dispersion.
[0075] Here, about the mixing amount of each component, in the obtained nanocellulose masterbatch of the present invention, the mode of becoming the above-mentioned range is that nanocellulose is made into 0.3-60 mass parts as solid content and dispersant is made into 0.5-35 mass parts as mixing amount relative to 100 mass parts of rubber components, and RF resin is made into 0.03-1.2 mass parts and formaldehyde is made into 0.02-0.8 mass parts as mixing amount relative to 1 mass part of nanocellulose. In the case of using an aqueous solution (formalin) as formaldehyde of RF latex, it is made into the above-mentioned range as the solid content of formaldehyde. Furthermore, mixing is carried out by a mixer, etc. to obtain a raw material dispersion in a slurry state.
[0076] In addition, the solid content concentration of the raw material dispersion is preferably 60% by mass or less, more preferably 2 to 50% by mass, and further preferably 5 to 50% by mass. If the solid content concentration exceeds 60% by mass, the stability of the raw material dispersion may be reduced. The same is true in the following production methods II to VII.
[0077] Furthermore, a coagulant is added while stirring the raw material dispersion to coagulate the polymer component, and the coagulant is roughly separated from the water by filtration, and the coagulant is washed as needed to remove the coagulant. Furthermore, the obtained coagulant is dried (for example, dried at 50 to 100° C. for 0.5 to 30 hours) to obtain a dried product. Through these steps, the nanocellulose masterbatch of the present invention is obtained.
[0078] Here, as the coagulant, an inorganic salt (sodium chloride, potassium chloride, etc.), an unsaturated fatty acid metal salt (acrylic acid metal salt, methacrylic acid metal salt, etc.), or the like can be used.
[0079] [Manufacturing method II]
[0080] In the manufacturing method II, first, rubber latex of natural rubber or styrene-butadiene copolymer rubber, RF latex, and nanocellulose are put into a mixer etc. at the same time. In addition, the solid content of rubber latex and RF latex, the nanocellulose content when a nanocellulose aqueous dispersion is used, and the blending amount of each component are the same as those of the manufacturing method I. Then, mixing is performed by a mixer etc. to obtain a raw material dispersion in a slurry state.
[0081] Furthermore, a coagulant is added while stirring the obtained raw material dispersion to coagulate the polymer component, and the coagulant is roughly separated from the water by filtration, and the coagulant is washed as needed to remove the coagulant. Furthermore, a dispersant is added to the obtained coagulant for mixing. Furthermore, the coagulant mixed with the dispersant is dried (for example, dried at 50 to 100° C. for 0.5 to 30 hours) to obtain a dried product. Through these steps, the nanocellulose masterbatch of the present invention is obtained. In addition, the mixing amount of the dispersant is adjusted in the same manner as in manufacturing method I. In addition, the preferred example of the coagulant is also the same as that of manufacturing method I.
[0082] [Manufacturing method III]
[0083] In the manufacturing method III, first, rubber latex of natural rubber or styrene-butadiene copolymer rubber, RF latex, and nanocellulose are also put into a mixer at the same time. In addition, the solid content of the rubber latex and RF latex, the nanocellulose content when the nanocellulose aqueous dispersion is used, and the mixing amount of each component are the same as those of the manufacturing method I. Then, mixing is performed by a mixer to obtain a raw material dispersion in a slurry state.
[0084] Furthermore, a coagulant is added while stirring the obtained raw material dispersion to coagulate the polymer component, and the coagulant is roughly separated from the water by filtration, and the coagulant is washed as needed to remove the coagulant. Furthermore, after the obtained coagulant is dried (for example, dried at 50 to 100° C. for 0.5 to 30 hours) to obtain a dried product, a dispersant is added to the dried product and mixed. Through these steps, the nanocellulose masterbatch of the present invention is obtained. In addition, the mixing amount of the dispersant is adjusted in the same manner as in the manufacturing method I. In addition, the preferred example of the coagulant is also the same as that of the manufacturing method I.
[0085] [Manufacturing method IV]
[0086] In the manufacturing method IV, first, RF latex, nanocellulose, and dispersant are put into a mixer or the like at the same time. In addition, the solid content of the RF latex, the nanocellulose content when a nanocellulose aqueous dispersion is used, and the blending amount of each component are the same as those of the manufacturing method I. Furthermore, mixing is performed by a mixer or the like to obtain a mixed solution. In this way, by mixing nanocellulose and RF latex before rubber latex, it is easier to perform surface treatment of nanocellulose based on RF resin and formaldehyde (the same is true for the manufacturing methods V to VII described later).
[0087] Furthermore, a rubber latex of natural rubber or styrene-butadiene copolymer rubber is added and mixed into the obtained mixed solution to obtain a raw material dispersion in a slurry state, a coagulant is added while stirring the raw material dispersion to coagulate the polymer component, and the coagulant is roughly separated from the water by filtration, and the coagulant is washed as needed to remove the coagulant. The coagulant is further dried (for example, dried at 50 to 100° C. for 0.5 to 30 hours) to obtain a dried product. Through these steps, the nanocellulose masterbatch of the present invention is obtained. In addition, the solid content of the rubber latex and the mixing amount of each component are adjusted in the same manner as in manufacturing method I. In addition, the preferred example of the coagulant is also the same as in manufacturing method I.
[0088] [Manufacturing method V]
[0089] In the manufacturing method V, first, RF latex and nanocellulose are put into a mixer at the same time. In addition, the solid content of the RF latex, the nanocellulose content when a nanocellulose aqueous dispersion is used, and the blending amount of each component are the same as those in the manufacturing method I. Then, mixing is performed by a mixer to obtain a mixed solution.
[0090] Furthermore, a rubber latex of natural rubber or styrene-butadiene copolymer rubber and a dispersant are added to the obtained mixed solution and mixed to obtain a raw material dispersion in a slurry state, a coagulant is added while stirring the raw material dispersion to coagulate the polymer component, and the coagulant is roughly separated from the water by filtration, and the coagulant is washed as needed to remove the coagulant. Further, the obtained coagulant is dried (for example, dried for 0.5 to 30 hours at 50 to 100° C.) to obtain a dried product. Through these steps, the nanocellulose masterbatch of the present invention is obtained. In addition, the solid content of the rubber latex and the mixing amount of each component are adjusted in the same manner as in manufacturing method I. In addition, the preferred example of the coagulant is also the same as in manufacturing method I.
[0091] [Manufacturing method VI]
[0092] In the manufacturing method VI, first, the RF latex and the nanocellulose are also put into a mixer at the same time. In addition, the solid content of the RF latex, the nanocellulose content when the nanocellulose aqueous dispersion is used, and the blending amount of each component are the same as those in the manufacturing method I. Then, mixing is performed by a mixer to obtain a mixed solution.
[0093] Furthermore, a rubber latex of natural rubber or styrene-butadiene copolymer rubber is added to the obtained mixed solution and mixed to obtain a raw material dispersion in a slurry state, a coagulant is added while stirring the raw material dispersion to coagulate the polymer component, and the coagulant is roughly separated from the water by filtration, and the coagulant is washed as needed to remove the coagulant. Further, a dispersant is added to the obtained coagulant for mixing. Furthermore, the coagulant mixed with the dispersant is dried (for example, dried for 0.5 to 30 hours under the conditions of 50 to 100° C.) to obtain a dried product. Through these steps, the nanocellulose masterbatch of the present invention is obtained. In addition, the solid content of the rubber latex and the mixing amount of each component are adjusted in the same manner as in the manufacturing method I. In addition, the preferred example of the coagulant is also the same as the manufacturing method I.
[0094] [Manufacturing method VII]
[0095] In the manufacturing method VII, first, the RF latex and the nanocellulose are also put into a mixer at the same time. In addition, the solid content of the RF latex, the nanocellulose content when the nanocellulose aqueous dispersion is used, and the blending amount of each component are the same as those of the manufacturing method I. Then, mixing is performed by a mixer to obtain a mixed solution.
[0096] Furthermore, a rubber latex of natural rubber or styrene-butadiene copolymer rubber is added and mixed into the obtained mixed solution to obtain a raw material dispersion in a slurry state, a coagulant is added while stirring the raw material dispersion to coagulate the polymer component, and the coagulant is roughly separated from the water by filtration, and the coagulant is washed as needed to remove the coagulant. Further, after the obtained coagulant is dried (for example, dried for 0.5 to 30 hours under the conditions of 50 to 100° C.) to obtain a dried product, a dispersant is added and mixed into the dried product. Through these steps, the nanocellulose masterbatch of the present invention is obtained. In addition, the solid content of the rubber latex and the mixing amount of each component are adjusted in the same manner as in the manufacturing method I. In addition, the preferred example of the coagulant is also the same as the manufacturing method I.
[0097] Here, in these manufacturing methods I to VII, it is necessary to put RF latex and nanocellulose into and mix them at the same time. Thus, as mentioned above, nanocellulose is surface-treated by the RF resin and formaldehyde contained in the RF latex. That is, it becomes a state where RF resin and the like are attached to at least a portion of the surface of the nanocellulose. At the same time, the styrene-butadiene copolymer rubber and / or styrene-butadiene-vinyl pyridine terpolymer contained in the RF latex are configured closely to the RF resin. Thus, when mixed with rubber latex, by the affinity of the rubber component of the rubber latex and the styrene-butadiene copolymer rubber and / or styrene-butadiene-vinyl pyridine terpolymer configured closely to the RF resin, as a result, the affinity of the rubber component of the rubber latex and the surface-treated nanocellulose is improved, and the nanocellulose can be dispersed homogeneously in the rubber component of the rubber latex under the state of being divided into nanometers.
[0098] Furthermore, the methods I to VII for producing the nanocellulose masterbatch of the present invention may include any steps related to the production of the rubber masterbatch in addition to the above steps, as long as the effects of the present invention are not affected. For example, the steps of mixing raw materials other than the above in the raw material dispersion, coagulant, dried product, etc. may be included.
[0099] The nanocellulose masterbatch of the present invention obtained in this manner is characterized in that nanocellulose is uniformly dispersed in the rubber component and the increase in viscosity thereof is suppressed (the viscosity is maintained low).
[0100] <Rubber composition of the present invention>
[0101] Next, the rubber composition of the present invention using the nanocellulose masterbatch of the present invention will be described in detail.
[0102] Use the nano cellulose masterbatch of the present invention, rubber component and carbon black and / or silicon dioxide as filler as raw material, further according to the need, appropriate amount of silane coupling agent, zinc oxide (acidified lead) (zinc oxide (lead)), stearic acid, bonding resin, adhesive, plasticizer, antioxidant, wax, processing aid, aromatic oil, lecithin, liquid polymer, terpene resin, thermosetting resin, vulcanizing agent (for example, sulfur), vulcanization accelerator, vulcanization accelerator etc. generally used in rubber composition various additives, can be mixed and kneaded by known method and obtain rubber composition of the present invention.Therefore, rubber composition of the present invention at least comprises rubber component, nano cellulose, dispersant and carbon black and / or silicon dioxide that surface treatment is carried out using RF resin and formaldehyde.In addition, about at least a part of the additive except vulcanizing agent, vulcanization accelerator and vulcanization accelerator, when making nano cellulose masterbatch of the present invention, can add mixing in raw material dispersion etc., make nano cellulose masterbatch of the present invention contain.
[0103] The content of carbon black and / or silica in the rubber composition of the present invention is 30 to 200 parts by mass relative to 100 parts by mass of all rubber components, more preferably 40 to 150 parts by mass, and further preferably 50 to 100 parts by mass. In addition, the content of nanocellulose (nanocellulose derived from the nanocellulose masterbatch of the present invention) in the rubber composition of the present invention is 0.3 to 60 parts by mass relative to 100 parts by mass of all rubber components, more preferably 0.5 to 40 parts by mass, further preferably 1 to 20 parts by mass, and further preferably 2 to 10 parts by mass. Furthermore, the content of RF resin and formaldehyde is the same as above as long as it is relative to the mass of nanocellulose. In addition, the so-called "100 parts by mass of all rubber components" refers to the case where the total mass of the rubber component derived from the nanocellulose masterbatch of the present invention and the rubber component used other than the nanocellulose masterbatch of the present invention is set to 100 parts by mass. The same is true below.
[0104] Here, the so-called "silicon dioxide" in the present invention refers to a particulate material composed of silicon dioxide (SiO2) or with silicon dioxide as the main component (for example, containing 80 mass % or more, and further 90 mass % or more), and the so-called "carbon black" refers to carbon particles with a diameter of about 3 to 500 nm produced through quality control in industry.
[0105] The silica and carbon black are not particularly limited, and any known silica and carbon black mixed in the rubber composition can be used. For example, as a specific example of silica, wet silica, dry silica, pyrogenic silica, diatomaceous earth, etc. can be cited, among which wet silica is preferably used. In addition, as a specific example of carbon black, various grades of carbon black such as SAF-HS, SAF, ISAF-HS, ISAF, ISAF-LS, IISAF-HS, HAF-HS, HAF, HAF-LS, FEF, etc. can be used. Furthermore, the silica and carbon black can be used alone or in combination of two or more.
[0106] In addition, in the rubber composition of the present invention, as fillers, components other than carbon black and silica, such as clay, aluminum hydroxide, calcium carbonate, mica, talc, aluminum oxide, titanium oxide, barium sulfate, lecithin, etc., can be used. These can be mixed alone or in combination.
[0107] And then, the rubber component of the rubber composition of the present invention is preferably a diene rubber, which is mixed with the nanocellulose masterbatch of the present invention. The diene rubber is a rubber component having a double bond in the polymer backbone, specifically, natural rubber (NR), butadiene rubber (BR), styrene-butadiene copolymer rubber (SBR), acrylonitrile-butadiene copolymer rubber (NBR), chloroprene rubber (CR), isoprene rubber (IR), styrene-isoprene copolymer rubber, isoprene-butadiene copolymer rubber, styrene-butadiene-vinyl pyridine terpolymer, etc. can be exemplified. And then, in the rubber composition of the present invention, such a diene rubber can be used alone or in combination of two or more.
[0108] Particularly suitable for using natural rubber and / or isoprene rubber as the rubber component mixed with the nanocellulose masterbatch of the present invention. In this case, the rubber composition of the present invention is preferably a composition comprising more than 25 mass parts of natural rubber and / or isoprene rubber among all rubber components 100 mass parts. That is, preferably among all rubber components 100 mass parts included by the rubber composition of the present invention, a composition comprising more than 25 mass parts of natural rubber, a composition comprising more than 25 mass parts of isoprene rubber, or any one of the compositions comprising more than 25 mass parts of natural rubber and isoprene rubber in total. In addition, the lower limit can be more than 30 mass parts, can also be more than 40 mass parts, can also be more than 50 mass parts. And then, in this case, the nanocellulose masterbatch of the present invention mixed in the rubber composition of the present invention preferably uses the latex of natural rubber as rubber latex to make (the rubber component included comprises natural rubber as the main component).
[0109] In addition, using styrene-butadiene copolymer rubber and / or styrene-butadiene-vinyl pyridine terpolymer as the rubber component mixed with the nanocellulose masterbatch of the present invention is also suitable. In this case, preferably the rubber composition of the present invention includes styrene-butadiene copolymer rubber and / or styrene-butadiene-vinyl pyridine terpolymer more than 35 mass parts among all rubber components 100 mass parts, and the mass ratio of styrene-butadiene copolymer rubber and / or styrene-butadiene-vinyl pyridine terpolymer in all rubber components becomes the highest structure. That is, preferably among all rubber components 100 mass parts included by the rubber composition of the present invention, the composition comprising more than 35 mass parts of styrene-butadiene copolymer rubber, the composition comprising more than 35 mass parts of styrene-butadiene-vinyl pyridine terpolymer, or the total of styrene-butadiene copolymer rubber and styrene-butadiene-vinyl pyridine terpolymer, or the mass ratio of any one of the total of styrene-butadiene copolymer rubber, styrene-butadiene-vinyl pyridine terpolymer and styrene-butadiene-vinyl pyridine terpolymer is the highest. In addition, this lower limit can be more than 40 mass parts, can be more than 50 mass parts. And then, in this case, the nanocellulose masterbatch of the present invention that is mixed in the rubber composition of invention preferably uses the latex of styrene-butadiene copolymer rubber as rubber latex to make (the rubber component included comprises styrene-butadiene copolymer rubber as principal component).
[0110] In addition, the rubber composition of the present invention can be a composition that only comprises the material derived from the nanocellulose masterbatch of the present invention as a rubber component. That is, the material comprising the rubber component can be used to make the rubber composition of the present invention without using the material comprising the rubber component except the nanocellulose masterbatch of the present invention. However, the nanocellulose masterbatch of the present invention is suppressed due to the viscosity rise, and the mixing with other rubber components is easily carried out, so it is very easy to use the nanocellulose masterbatch of the present invention and other rubber components to make the rubber composition of the present invention.
[0111] And then, the manufacture method of rubber composition of the present invention is not particularly limited as long as according to ordinary method.As an example of manufacture method, nanocellulose masterbatch of the present invention, rubber component, carbon black and / or silicon dioxide and other components as required are used to carry out specified amount mixing, mixing at normal temperature or high temperature using mixing machines such as Banbury mixer, kneader, roller, thereby rubber composition of the present invention can be manufactured.In addition, when using vulcanization system composition (sulfur, vulcanization accelerator, vulcanization accelerating auxiliary agent etc.), preferably the composition beyond it is first mixed at high temperature, and the vulcanization system composition is mixed after cooling.
[0112] About the rubber composition of the present invention obtained by such operation, the nanocellulose derived from the nanocellulose masterbatch of the present invention is homogeneously dispersed in the rubber component and kept to be divided into nanometer-level state, and tensile stress and elongation are excellent. In addition, as mentioned above, the mixing of the nanocellulose masterbatch of the present invention used by the rubber composition of the present invention and other materials is easy to carry out, and the preparation of the rubber composition of the present invention is very easy.
[0113] Hereinafter, embodiments of the present invention will be described, but the present invention is not limited to the following embodiments, and various modifications are possible within the technical concept of the present invention.
[0114] Example
[0115] (Example 1: Preparation and evaluation of nanocellulose masterbatch 1)
[0116] A rubber latex of natural rubber (HYTEX HA, high ammonia type, solid content concentration 60% by mass, manufactured by SIME DARBYPLANTATION SDN BHD), a novolac type resorcinol-formaldehyde initial condensate (RF resin (Sumikanool (registered trademark) 700S), manufactured by Sumitomo Chemical Industries, Ltd.) and a formaldehyde aqueous solution (37% solution, manufactured by Kanto Chemical Co., Ltd.) were mixed with a styrene-butadiene copolymer rubber latex (Nipol LX112, solid content concentration 40.5% by mass, manufactured by Nippon Zeon Co., Ltd.) Aqueous dispersion (solid content 1.0% by mass) of oxidized cellulose nanofibers (CNF; Cellenpia, manufactured by Nippon Paper Industries, Ltd.), and a dispersant were mixed and dispersed by changing the timing of adding the rubber latex or the timing of adding the dispersant so that the solid content amount would be the mass ratio shown in the upper section of the following Table 1, thereby obtaining each raw material dispersion in a slurry state with a solid content concentration of 60% or less. The RF latex was mixed so that the solid content of the styrene-butadiene copolymer rubber was 90% by mass and the solid content of the RF resin and formaldehyde was 10% by mass.
[0117] Furthermore, each raw material dispersion was coagulated by salting out using sodium chloride as a coagulant, and the coagulant was further recovered and washed and dried. If necessary, a dispersant was added to any of these steps for mixing, and nanocellulose masterbatches of E1-1 to E1-11 and C1-1 to C1-7 were obtained. In addition, the above washing was repeated 5 times while filtering under reduced pressure with a Buchner funnel while spreading distilled water on the surface of the coagulant to wash away the sodium chloride. In addition, the above drying was carried out by spreading the washed coagulant in a dish and placing it in a constant temperature dryer at 70°C for 24 hours.
[0118] The Mooney viscosity of each of the obtained nanocellulose masterbatches was measured in accordance with JIS K6300-1: 2013. Specifically, the Mooney viscosity was measured using a Mooney viscometer using an L-type rotor (38.1 mm diameter, 5.5 mm thickness) under the conditions of a preheating time of 1 minute, a rotor rotation time of 4 minutes, 100°C, and 2 rpm. Furthermore, each of the coagulated and dried nanocellulose masterbatches was observed by a transmission electron microscope (TEM), and an electron microscope image was obtained by setting an appropriate magnification to confirm the state of the rubber component and the nanocellulose.
[0119] The results are shown in the lower part of the following Table 1. In addition, the Mooney viscosity is shown as a relative value (index expression (%)) when the data of the nanocellulose masterbatch of C1-1 is set as 100.
[0120]
[0121] The details of the dispersant and the timing of adding the rubber latex and the timing of adding the dispersant in the above Table 1 are as follows.
[0122] <Dispersant>
[0123] Dispersant 1: A mixture of calcium soap, saturated fatty acid amide, and saturated fatty acid ester (Storaktor HT204, manufactured by Storaktor Co., Ltd.)
[0124] Dispersant 2: A fatty acid derivative mixture containing zinc soap as a main component (Storaktor EF44, manufactured by Storaktor Co., Ltd.)
[0125] Dispersant 3: A mixture of saturated fatty acid zinc salt, aliphatic hydrocarbon, and an inorganic filler (Acchiplaster ST, manufactured by Lanxess Co., Ltd.)
[0126] ※All are mixtures of fatty acid derivatives containing metal soap as the main ingredient
[0127] <Timing of adding rubber latex>
[0128] Same as CNF: Rubber latex, CNF aqueous dispersion, and RF latex are added and mixed at the same time.
[0129] Different from CNF: CNF aqueous dispersion and RF latex are mixed and then added to rubber latex.
[0130] <Timing of adding dispersant>
[0131] I: The rubber latex, CNF aqueous dispersion, RF latex, and dispersant are all added and mixed at the same time.
[0132] II: Rubber latex, CNF aqueous dispersion, and RF latex are added and mixed at the same time, and after coagulation, a dispersant is added and mixed.
[0133] III: Rubber latex, CNF aqueous dispersion, and RF latex are added and mixed at the same time, coagulated, and further dried, and then a dispersant is added and mixed.
[0134] IV: After the CNF aqueous dispersion, RF latex, and dispersant are added and mixed at the same time, the rubber latex is added and mixed.
[0135] V: After the CNF aqueous dispersion and the RF latex are mixed, a dispersant is added to the mixed solution at the same time as the rubber latex and mixed.
[0136] VI: After the CNF aqueous dispersion and the RF latex are mixed, rubber latex is added to the mixed solution and coagulated, and then a dispersant is added and mixed.
[0137] VII: After the CNF aqueous dispersion and the RF latex are mixed, rubber latex is added to the mixed solution, coagulated, and further dried, and then a dispersant is added and mixed.
[0138] In addition, with reference to the electron microscope image, regarding C1-6 (nanocellulose masterbatch not containing RF resin, formaldehyde, and dispersant) and E1-1 (nanocellulose masterbatch containing RF resin, formaldehyde, and dispersant), schematic diagrams schematically showing the state after coagulation and drying are shown in Figure 1 (a) is C1-6, (b) is E1-1, nanocellulose (NC) is represented by a line, the rubber component is represented by a large circle, and the dispersant is represented by a small circle.
[0139] This result shows that the nanocellulose in the nanocellulose masterbatches of E1-1 to E1-11 and C1-4 to C1-5 is homogeneously dispersed and the increase in viscosity is suppressed.
[0140] (Example 2: Preparation and Evaluation of Rubber Composition 1)
[0141] Rubber compositions having the compositions shown in Table 2 below were prepared.
[0142] Specifically, using each nanocellulose masterbatch (MB) obtained in Example 1, in the form of the mass ratio shown in the upper layer of Table 2 below as the solid content, the components other than sulfur, vulcanization accelerator, and vulcanization accelerator are mixed with a closed Banbury mixer, and after a specified time, they are discharged from the mixer and cooled at room temperature. Next, using an open roller, sulfur, vulcanization accelerator, and vulcanization accelerator are mixed and mixed, and they are pressurized and vulcanized at 160 ° C for 15 minutes in a mold of 15 cm × 15 cm × 0.2 cm to produce vulcanized rubber test pieces (rubber compositions) of E2-1 to E2-12 and C2-1 to C2-7. In addition, as Reference Example 1, a vulcanized rubber test piece produced by the same operation except that nanocellulose masterbatch is not used is also obtained. Furthermore, each of the obtained vulcanized rubber test pieces was subjected to a tensile test at a tensile speed of 500 mm / min in accordance with JIS K6251:2010, and the tensile stress at 100% elongation (M100: MPa) and the elongation at break (= elongation at break: Eb) were measured at room temperature (20°C).
[0143] The results are shown in the lower part of the following Table 2. M100 and Eb are both shown as relative values (index expression (%)) with the data of the rubber composition of C2-1 being 100.
[0144]
[0145] The details of each component in the above Table 2 are as follows.
[0146] Natural rubber (NR): TSR20
[0147] ·Carbon black: Sewage Fluid N339 (manufactured by Sinotech Co., Ltd.)
[0148] Silica: Zeosil 1165MP (manufactured by Rolldia Co., Ltd.)
[0149] Silane coupling agent: Si69 (bis(3-triethoxysilylpropyl)tetrasulfide, manufactured by Ebonick Degussa Co., Ltd.)
[0150] Zinc oxide: ZnO (manufactured by Shodo Chemical Industry Co., Ltd.)
[0151] · Stearic acid: stearic acid (manufactured by NOF Corporation)
[0152] Antioxidant: SANTOFLEX 6PPD (manufactured by Flexsys)
[0153] ·Wax: Paraffin wax (manufactured by Ouchi Shinko Chemical Industry Co., Ltd.)
[0154] ·Fragrance oil: Ekostor No. 4S (manufactured by Showa Seiko Oil Co., Ltd.)
[0155] Sulfur: Jinhua ink-infused micronized sulfur (manufactured by Tsurumi Chemical Industry Co., Ltd.)
[0156] · Vulcanization accelerator: Noxelara CZ-G (manufactured by Ouchi Shinko Chemical Industry Co., Ltd.)
[0157] · Vulcanization accelerator: Soxhinolide DG (manufactured by Sumitomo Chemical Co., Ltd.)
[0158] These results show that the rubber compositions E2-1 to E2-12 are excellent in both tensile stress and elongation.
[0159] (Example 3: Preparation and evaluation of nanocellulose masterbatch 2)
[0160] The rubber latex of natural rubber, RF latex, and aqueous dispersion of oxidized cellulose nanofibers were the same as those in Example 1, and they were mixed and dispersed with the dispersant in such a manner that the solid content became the mass ratio shown in the upper layer of the following Table 3, while changing the timing of adding the rubber latex or the timing of adding the dispersant, to obtain each raw material dispersion in a slurry state with a solid content concentration of less than 60% by mass.
[0161] Furthermore, each raw material dispersion liquid was coagulated and dried in the same manner as in Example 1 to obtain nanocellulose masterbatches E3-1 to E3-11 and C3-1 to C3-7.
[0162] The Mooney viscosity of each of the obtained nanocellulose masterbatches was measured in the same manner as in Example 1. The results are shown in the lower portion of Table 3. The Mooney viscosity is shown as a relative value (index (%)) with the data of the nanocellulose masterbatch C3-1 being 100.
[0163]
[0164] The details of the dispersant in Table 3 are as follows. The details of the timing of adding the rubber latex and the timing of adding the dispersant are the same as those in Example 1.
[0165] <Dispersant>
[0166] Dispersant 4: Liquid polyisoprene having a weight average molecular weight of 47,000 (Claraprene LIR-50, manufactured by Clara Corporation)
[0167] Dispersant 5: Liquid polybutadiene with a weight average molecular weight of 3,900 (RICON 150, manufactured by Kuray Bare Co., Ltd.)
[0168] Dispersant 6: Maleic acid-modified liquid polybutadiene having a weight average molecular weight of 3100 (RICON130MA20, manufactured by Kuray Bare Co., Ltd.)
[0169] ※All are low molecular weight diene liquid polymers with a weight average molecular weight of 2000 or more and 60000 or less
[0170] This result shows that the nanocellulose masterbatches of E3-1 to E3-11 and C3-4 to C3-5 suppress the increase in viscosity.
[0171] (Example 4: Preparation and Evaluation of Rubber Composition 2)
[0172] Rubber compositions having the compositions shown in Table 4 below were prepared.
[0173] Specifically, each nanocellulose masterbatch (MB) obtained in Example 3 was used to prepare vulcanized rubber test pieces (rubber compositions) of E4-1 to E4-12, C4-1 to C4-7, and Reference Example 1 in the same manner as in Example 2, so that the solid content was the mass ratio shown in the upper layer of the following Table 4. Furthermore, for each of the obtained vulcanized rubber test pieces, the tensile stress at 100% elongation (M100: MPa) and the elongation at break (= elongation at break: Eb) were measured at room temperature (20°C) in the same manner as in Example 2.
[0174] The results are shown in the lower part of the following Table 4. M100 and Eb are both shown as relative values (index expression (%)) when the data of the rubber composition of C4-1 is set to 100. The details of each component in the following Table 4 are the same as those in Table 2 of Example 2.
[0175]
[0176] These results show that the rubber compositions E4-1 to E4-12 are excellent in both tensile stress and elongation.
[0177] (Example 5: Preparation and Evaluation of Nanocellulose Masterbatch 3)
[0178] The rubber latex of natural rubber, RF latex, and aqueous dispersion of oxidized cellulose nanofibers were the same as those in Example 1, and they were mixed and dispersed with a dispersant in such a manner that the solid content became the mass ratio shown in the upper layer of the following Table 5, while changing the timing of adding the rubber latex or the timing of adding the dispersant to obtain each raw material dispersion in a slurry state with a solid content concentration of less than 60% by mass.
[0179] Furthermore, each of the raw material dispersions was coagulated and dried in the same manner as in Example 1 to obtain nanocellulose masterbatches of E5-1 to E5-11 and C5-1 to C5-7.
[0180] The Mooney viscosity of each of the obtained nanocellulose masterbatches was measured in the same manner as in Example 1. The results are shown in the lower portion of Table 3. The Mooney viscosity is shown as a relative value (index (%)) when the data of the nanocellulose masterbatch C5-1 is set to 100.
[0181]
[0182] The details of the dispersant in Table 5 are as follows. The timing of adding the rubber latex and the timing of adding the dispersant are the same as those in Example 1.
[0183] <Dispersant>
[0184] ·Dispersant 7: Fragrance oil (Escortoro No. 4S, manufactured by Showa Seiko Oil Co., Ltd.)
[0185] Dispersant 8: Rosin resin (rosin (China rosin WW), manufactured by Arakawa Chemical Industries, Ltd.)
[0186] Dispersant 9: coumarone-indene resin (Nitrogen G-90, manufactured by Nippon Paint Chemical Co., Ltd.)
[0187] This result shows that the nanocellulose masterbatches of E5-1 to E5-11 and C5-4 to C5-5 suppress the increase in viscosity.
[0188] (Example 6: Preparation and Evaluation of Rubber Composition 3)
[0189] Rubber compositions having the compositions shown in Table 6 below were prepared.
[0190] Specifically, each nanocellulose masterbatch (MB) obtained in Example 5 was used to prepare vulcanized rubber test pieces (rubber compositions) of E6-1 to E6-12, C6-1 to C6-7, and Reference Example 1 in the same manner as in Example 2, so that the solid content was the mass ratio shown in the upper layer of the following Table 6. Furthermore, for each of the obtained vulcanized rubber test pieces, the tensile stress at 100% elongation (M100: MPa) and the elongation at break (= elongation at break: Eb) were measured at room temperature (20°C) in the same manner as in Example 2.
[0191] The results are shown in the lower part of the following Table 6. M100 and Eb are both shown as relative values (index expression (%)) when the data of the rubber composition of C6-1 is set to 100. The details of each component in the following Table 6 are the same as those in Table 2 of Example 2.
[0192]
[0193] These results show that the rubber compositions E6-1 to E6-12 are excellent in both tensile stress and elongation.
[0194] (Example 7: Preparation and Evaluation of Nanocellulose Masterbatch 4)
[0195] A rubber latex of a styrene-butadiene copolymer rubber (Nipol LX112, solid content concentration 40.5% by mass, manufactured by Nippon Zeon Co., Ltd.), a RF latex obtained by mixing a novolac type resorcinol-formaldehyde initial condensate (RF resin (Sumikanool (registered trademark) 700S, manufactured by Sumitomo Chemical Industries, Ltd.) and an aqueous formaldehyde solution (37% solution, manufactured by Kanto Chemical Co., Ltd.) with a latex of a styrene-butadiene copolymer rubber (Nipol LX112, solid content concentration 40.5% by mass, manufactured by Nippon Zeon Co., Ltd.), an aqueous dispersion (solid content 1.0% by mass) of oxidized cellulose nanofibers (CNF; Cellenpia, manufactured by Nippon Paper Industries, Ltd.), and a dispersant were mixed and dispersed by changing the timing of adding the rubber latex or the timing of adding the dispersant so that the solid content amount would be the mass ratio shown in the upper section of the following Table 7, to obtain each raw material dispersion in a slurry state with a solid content concentration of 60% or less. The RF latex was mixed so that the solid content of the styrene-butadiene copolymer rubber was 90% by mass and the solid content of the RF resin and formaldehyde was 10% by mass.
[0196] Furthermore, each raw material dispersion was coagulated by salting out using sodium chloride as a coagulant, and the coagulant was recovered and washed and dried. If necessary, a dispersant was added in any of these steps to mix the nanocellulose masterbatches E7-1 to E7-11 and C7-1 to C7-7. The washing and drying were performed in the same manner as in Example 1.
[0197] The Mooney viscosity of each of the obtained nanocellulose masterbatches was measured in the same manner as in Example 1. The results are shown in the lower portion of Table 7. The Mooney viscosity is shown as a relative value (index (%)) with the data of the nanocellulose masterbatch of C7-1 being 100.
[0198] In addition, the details of the dispersant, the timing of adding the rubber latex, and the timing of adding the dispersant in the following Table 7 are the same as those in Example 1.
[0199]
[0200] This result shows that the nanocellulose masterbatches of E7-1 to E7-11 and C7-4 to C7-5 suppress the increase in viscosity.
[0201] (Example 8: Preparation and Evaluation of Rubber Composition 4)
[0202] Rubber compositions having the compositions shown in Table 8 below were prepared.
[0203] Specifically, using each nanocellulose masterbatch (MB) obtained in Example 7, in the form of the mass ratio shown in the upper layer of Table 8 below as the solid content, the components other than sulfur, vulcanization accelerator, and vulcanization accelerator are mixed with a closed Banbury mixer, and after a specified time, they are discharged from the mixer and cooled at room temperature. Next, using an open roller, sulfur, vulcanization accelerator, and vulcanization accelerator are mixed and mixed, and they are pressurized and vulcanized at 160 ° C for 15 minutes in a mold of 15 cm × 15 cm × 0.2 cm to produce vulcanized rubber test pieces (rubber compositions) of E8-1 to E8-12 and C8-1 to C8-7. In addition, as Reference Example 2, a vulcanized rubber test piece produced by the same operation except that the nanocellulose masterbatch is not used is also obtained. Furthermore, for each of the obtained vulcanized rubber test pieces, the tensile stress at 100% elongation (M100: MPa) and the elongation at break (= elongation at break: Eb) were measured at room temperature (20°C) in the same manner as in Example 2.
[0204] The results are shown in the lower part of the following Table 8. M100 and Eb are both shown as relative values (index expression (%)) with the data of the rubber composition of C8-1 being 100.
[0205]
[0206] The details of each component in the above Table 8 are as follows.
[0207] Styrene-butadiene copolymer rubber (SBR): Nipol 1502 (manufactured by Nippon Zeon Co., Ltd.)
[0208] ·Carbon black: Sewage Fluid N339 (manufactured by Sinotech Co., Ltd.)
[0209] Silica: Zeosil 1165MP (manufactured by Rolldia Co., Ltd.)
[0210] Silane coupling agent: Si69 (bis(3-triethoxysilylpropyl)tetrasulfide, manufactured by Ebonick Degussa Co., Ltd.)
[0211] Zinc oxide: ZnO (manufactured by Shodo Chemical Industry Co., Ltd.)
[0212] · Stearic acid: stearic acid (manufactured by NOF Corporation)
[0213] Antioxidant: SANTOFLEX 6PPD (manufactured by Flexsys)
[0214] ·Wax: Paraffin wax (manufactured by Ouchi Shinko Chemical Industry Co., Ltd.)
[0215] ·Fragrance oil: Ekostor No. 4S (manufactured by Showa Seiko Oil Co., Ltd.)
[0216] Sulfur: Jinhua ink-infused micronized sulfur (manufactured by Tsurumi Chemical Industry Co., Ltd.)
[0217] · Vulcanization accelerator: Noxelara CZ-G (manufactured by Ouchi Shinko Chemical Industry Co., Ltd.)
[0218] · Vulcanization accelerator: Soxhinolide DG (manufactured by Sumitomo Chemical Co., Ltd.)
[0219] These results show that the rubber compositions E8-1 to E8-12 are excellent in both tensile stress and elongation.
[0220] (Example 9: Preparation and Evaluation of Nanocellulose Masterbatch 5)
[0221] The rubber latex of styrene-butadiene copolymer rubber, RF latex, and aqueous dispersion of oxidized cellulose nanofibers are the same as those in Example 7, and are mixed and dispersed with a dispersant in such a manner that the solid content becomes the mass ratio shown in the upper layer of the following Table 9 by changing the timing of adding the rubber latex or the timing of adding the dispersant, thereby obtaining each raw material dispersion in a slurry state with a solid content concentration of less than 60% by mass.
[0222] Furthermore, each of the raw material dispersions was coagulated and dried in the same manner as in Example 7 to obtain nanocellulose masterbatches of E9-1 to E9-11 and C9-1 to C9-7.
[0223] The Mooney viscosity of each of the obtained nanocellulose masterbatches was measured by the same method as in Example 1. The results are shown in the lower part of the following Table 9. The Mooney viscosity is expressed as a relative value (index expression (%)) when the data of the nanocellulose masterbatch of C9-1 is set to 100.
[0224] In addition, the details of the dispersant, the timing of adding the rubber latex, and the timing of adding the dispersant in the following Table 9 are the same as those in Example 3.
[0225]
[0226] This result shows that the nanocellulose masterbatches of E9-1 to E9-11 and C9-4 to C9-5 suppress the increase in viscosity.
[0227] (Example 10: Preparation and Evaluation of Rubber Composition 5)
[0228] Rubber compositions having the compositions shown in Table 10 below were prepared.
[0229] Specifically, each nanocellulose masterbatch (MB) obtained in Example 9 was used to prepare vulcanized rubber test pieces (rubber compositions) of E10-1 to E10-12, C10-1 to C10-7, and Reference Example 2 in the same manner as in Example 8, so that the solid content was the mass ratio shown in the upper layer of the following Table 10. Furthermore, for each of the obtained vulcanized rubber test pieces, the tensile stress at 100% elongation (M100: MPa) and the elongation at break (= elongation at break: Eb) were measured at room temperature (20°C) in the same manner as in Example 2.
[0230] The results are shown in the lower part of the following Table 10. M100 and Eb are both shown as relative values (index expression (%)) when the data of the rubber composition of C10-1 is set to 100. The details of each component in the following Table 10 are the same as those in Table 8 of Example 8.
[0231]
[0232] These results show that the rubber compositions of E10-1 to E10-12 are excellent in both tensile stress and elongation.
[0233] (Example 11: Preparation and Evaluation of Nanocellulose Masterbatch 6)
[0234] The rubber latex of styrene-butadiene copolymer rubber, RF latex, and aqueous dispersion of oxidized cellulose nanofibers are the same as those in Example 7, and are mixed and dispersed with a dispersant in such a manner that the solid content becomes the mass ratio shown in the upper layer of the following Table 11 by changing the timing of adding the rubber latex or the timing of adding the dispersant, thereby obtaining each raw material dispersion in a slurry state with a solid content concentration of less than 60% by mass.
[0235] Furthermore, each of the raw material dispersions was coagulated and dried in the same manner as in Example 7 to obtain nanocellulose masterbatches of E11-1 to E11-11 and C11-1 to C11-7.
[0236] The Mooney viscosity of each of the obtained nanocellulose masterbatches was measured in the same manner as in Example 1. The results are shown in the lower portion of Table 11. The Mooney viscosity is expressed as a relative value (index expression (%)) with the data of the nanocellulose masterbatch of C11-1 being 100.
[0237] In addition, the details of the dispersant, the timing of adding the rubber latex, and the timing of adding the dispersant in the following Table 11 are the same as those in Example 5.
[0238]
[0239] This result shows that the nanocellulose masterbatches of E11-1 to E11-11 and C11-4 to C11-5 suppress the increase in viscosity.
[0240] (Example 12: Preparation and Evaluation of Rubber Composition 6)
[0241] Rubber compositions having the compositions shown in Table 12 below were prepared.
[0242] Specifically, each nanocellulose masterbatch (MB) obtained in Example 11 was used to prepare vulcanized rubber test pieces (rubber compositions) of E12-1 to E12-12, C12-1 to C12-7, and Reference Example 2 in the same manner as in Example 8, so that the solid content was the mass ratio shown in the upper layer of the following Table 12. Furthermore, for each of the obtained vulcanized rubber test pieces, the tensile stress at 100% elongation (M100: MPa) and the elongation at break (= elongation at break: Eb) were measured at room temperature (20°C) in the same manner as in Example 2.
[0243] The results are shown in the lower part of Table 12 below. M100 and Eb are both shown as relative values (index expression (%)) when the data of the rubber composition of C12-1 is set to 100. The details of each component in Table 12 below are the same as those in Table 8 of Example 8.
[0244]
[0245] These results show that the rubber compositions E12-1 to E12-12 are excellent in both tensile stress and elongation.
[0246] This application claims priority based on Japanese patent application No. 2021-065158, filed on April 7, 2021, the disclosure of which is incorporated herein in its entirety.
Claims
1. A nanocellulose masterbatch comprising a rubber component, surface-treated nanocellulose, and a dispersant, Nanocellulose is surface treated by mixing with RF latex. The RF latex is composed of a latex of a styrene-butadiene copolymer rubber and / or a styrene-butadiene-vinyl pyridine terpolymer, a resol type and / or a novolac type resorcinol-formaldehyde initial condensate, and formaldehyde. In addition, in the RF latex, based on the solid content, the styrene-butadiene copolymer rubber and / or styrene-butadiene-vinyl pyridine terpolymer is 70-95% by mass, the resol type phenolic resin and / or novolac type resorcinol-formaldehyde initial condensate is 4-24% by mass, and the formaldehyde is 1-6% by mass. The rubber component contains natural rubber or styrene-butadiene copolymer rubber as a main component, The dispersant is a fatty acid derivative mixture containing a metal soap as a main component, or a fatty acid derivative mixture containing a fatty acid amide or a fatty acid ester, The nanocellulose is contained in an amount of 0.3 to 60 parts by mass and the dispersant is contained in an amount of 0.5 to 10 parts by mass with respect to 100 parts by mass of the rubber component. The present invention contains 0.03 to 1.2 parts by mass of the resol type and / or novolac type resorcinol-formaldehyde initial condensate and 0.02 to 0.8 parts by mass of the formaldehyde, based on 1 part by mass of the nanocellulose.
2. A nanocellulose masterbatch comprising a rubber component, surface-treated nanocellulose, and a dispersant, Nanocellulose is surface treated by mixing with RF latex. The RF latex is composed of a latex of a styrene-butadiene copolymer rubber and / or a styrene-butadiene-vinyl pyridine terpolymer, a resol type and / or a novolac type resorcinol-formaldehyde initial condensate, and formaldehyde. Furthermore, in the RF latex, based on the solid content, the styrene-butadiene copolymer rubber and / or styrene-butadiene-vinyl pyridine terpolymer accounts for 70 to 95% by mass, the resol type and / or novolac type resorcinol-formaldehyde initial condensate accounts for 4 to 24% by mass, and the formaldehyde accounts for 1 to 6% by mass, and the rubber component contains natural rubber or styrene-butadiene copolymer rubber as a main component. The dispersant is a low molecular weight diene liquid polymer having a weight average molecular weight of 2000 or more and 60000 or less, The nanocellulose is contained in an amount of 0.3 to 60 parts by mass and the dispersant is contained in an amount of 1 to 35 parts by mass relative to 100 parts by mass of the rubber component. The present invention contains 0.03 to 1.2 parts by mass of the resol type and / or novolac type resorcinol-formaldehyde initial condensate and 0.02 to 0.8 parts by mass of the formaldehyde, based on 1 part by mass of the nanocellulose.
3. A nanocellulose masterbatch comprising a rubber component, surface-treated nanocellulose, and a dispersant, Nanocellulose is surface treated by mixing with RF latex. The RF latex is composed of a latex of a styrene-butadiene copolymer rubber and / or a styrene-butadiene-vinyl pyridine terpolymer, a resol type and / or a novolac type resorcinol-formaldehyde initial condensate, and formaldehyde. Furthermore, in the RF latex, based on the solid content, the styrene-butadiene copolymer rubber and / or styrene-butadiene-vinyl pyridine terpolymer accounts for 70 to 95% by mass, the resol type and / or novolac type resorcinol-formaldehyde initial condensate accounts for 4 to 24% by mass, and the formaldehyde accounts for 1 to 6% by mass, and the rubber component contains natural rubber or styrene-butadiene copolymer rubber as a main component. The dispersant is one or more selected from oil, alkylphenol-formaldehyde resin, petroleum resin, rosin, rosin-modified resin, coumarone-indene resin, terpene resin, and lignin. The present invention comprises 0.3 to 60 parts by mass of the nanocellulose and 1 to 30 parts by mass of the dispersant relative to 100 parts by mass of the rubber component. The present invention contains 0.03 to 1.2 parts by mass of the resol type and / or novolac type resorcinol-formaldehyde initial condensate and 0.02 to 0.8 parts by mass of the formaldehyde, based on 1 part by mass of the nanocellulose.
4. A method for producing a nanocellulose masterbatch, which is the method for producing a nanocellulose masterbatch according to any one of claims 1 to 3, comprising the following steps: A process of mixing a rubber latex of natural rubber or styrene-butadiene copolymer rubber, a latex of a styrene-butadiene copolymer rubber and / or a styrene-butadiene-vinylpyridine terpolymer, a resol type and / or novolac type resorcinol-formaldehyde initial condensate, and an RF latex composed of formaldehyde, nanocellulose, and a dispersant to obtain a raw dispersion; a process of coagulating the raw dispersion to obtain a coagulant; and a process of drying the coagulant to obtain a dried product.
5. A method for producing a nanocellulose masterbatch, which is the method for producing a nanocellulose masterbatch according to any one of claims 1 to 3, comprising the following steps: A process of mixing a rubber latex of natural rubber or styrene-butadiene copolymer rubber, a latex of a styrene-butadiene copolymer rubber and / or a styrene-butadiene-vinylpyridine terpolymer, a resol type and / or novolac type resorcinol-formaldehyde initial condensate, and a RF latex composed of formaldehyde, and nanocellulose to obtain a raw dispersion; a process of coagulating the raw dispersion to obtain a coagulant, and then mixing a dispersant; and a process of drying the coagulant mixed with the dispersant to obtain a dried product.
6. A method for producing a nanocellulose masterbatch, the method for producing a nanocellulose masterbatch according to any one of claims 1 to 3, comprising the following steps: A process of mixing a rubber latex of natural rubber or styrene-butadiene copolymer rubber, a latex of a styrene-butadiene copolymer rubber and / or a styrene-butadiene-vinylpyridine terpolymer, a resol type and / or novolac type resorcinol-formaldehyde initial condensate, and a RF latex composed of formaldehyde, and nanocellulose to obtain a raw dispersion; a process of coagulating the raw dispersion to obtain a coagulant; and a process of drying the coagulant to obtain a dried product, and then mixing a dispersant.
7. A method for producing a nanocellulose masterbatch, the method for producing a nanocellulose masterbatch according to any one of claims 1 to 3, comprising the following steps: A process of mixing a latex of styrene-butadiene copolymer rubber and / or styrene-butadiene-vinylpyridine terpolymer, a resol type and / or novolac type resorcinol-formaldehyde initial condensate, and formaldehyde, a RF latex, nanocellulose, and a dispersant to obtain a mixed solution; a process of coagulating a raw material dispersion obtained by mixing a rubber latex of natural rubber or styrene-butadiene copolymer rubber with the mixed solution to obtain a coagulant; and a process of drying the coagulant to obtain a dried product.
8. A method for producing a nanocellulose masterbatch, the method for producing a nanocellulose masterbatch according to any one of claims 1 to 3, comprising the following steps: A process of mixing a latex of styrene-butadiene copolymer rubber and / or styrene-butadiene-vinylpyridine terpolymer, a resol type and / or novolac type resorcinol-formaldehyde initial condensate, and RF latex composed of formaldehyde, and nanocellulose to obtain a mixed solution; a process of coagulating a raw material dispersion obtained by mixing a rubber latex of natural rubber or styrene-butadiene copolymer rubber and a dispersant in the mixed solution to obtain a coagulant; and a process of drying the coagulant to obtain a dried product.
9. A method for producing a nanocellulose masterbatch, the method for producing a nanocellulose masterbatch according to any one of claims 1 to 3, comprising the following steps: A process of mixing a latex of styrene-butadiene copolymer rubber and / or styrene-butadiene-vinylpyridine terpolymer, a resol type and / or novolac type resorcinol-formaldehyde initial condensate, and RF latex composed of formaldehyde, and nanocellulose to obtain a mixed solution; a process of coagulating a raw material dispersion obtained by mixing a rubber latex of natural rubber or styrene-butadiene copolymer rubber with the mixed solution to obtain a coagulant, and then mixing a dispersant; and a process of drying the coagulant mixed with the dispersant to obtain a dried product.
10. A method for producing a nanocellulose masterbatch, the method for producing a nanocellulose masterbatch according to any one of claims 1 to 3, comprising the following steps: A process of mixing a latex of styrene-butadiene copolymer rubber and / or styrene-butadiene-vinylpyridine terpolymer, a resol type and / or novolac type resorcinol-formaldehyde initial condensate, and RF latex composed of formaldehyde, and nanocellulose to obtain a mixed solution; a process of coagulating a raw material dispersion obtained by mixing a rubber latex of natural rubber or styrene-butadiene copolymer rubber with the mixed solution to obtain a coagulant; and a process of drying the coagulant to obtain a dried product, and then mixing a dispersant.
Citation Information
Patent Citations
Installing structure of steering supporting member of vehicle
JP1988053169A
Chronic pain model mouse production method and screening method of medicament candidate
JP2021065158A
Rubber composition and tire using same
CN102378787A
Rubber composition and method for producing same
CN104144979A